Molly Post: capstone - Post, Molly, artist (Colorado State University. Libraries, 2013)
The artist's statement: "We stand in greater need of diverse, changing relationships than we do of things. We need people, and their words and thoughts, and desires and sufferings. These are the true elements that constitute the human environment." - Eulalia Bosch, The Pleasure of Beholding. My pots bring to light the beauty in the process of practice as daily ritual and the human experience of the environment. My pieces focus on the interplay between the practice of the processes of wheel throwing and choreographing as expression of movement. The two processes, although seemingly different, coexist to me personally as a continually evolving discussion that influences human interaction and experience of the physical world. The act of making, with its physical repetition of practice, records the movement of the body. I articulate this idea through my use of a repeating rhythmic pinched pattern as well as subtle details in line and color. The movement of dance, existing in a fluid realm of time and perception, speaks to the visual movement of my pottery, perceived by the eye as well as experienced through the hand of the user. My pots also connect my own personal practice and daily rituals to the viewer through experience of the objects of ritual in the environment of a meal. By embracing the warmth and familiarity of a family meal in the home, my pots evoke a timelessness through memory and a pleasurable lightness. Seeking to bring meaning beyond simply existing as objects, my pots invite human interaction through serving vessels, asking the user to humbly participate through a daily ritual of connecting and sharing.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.